Pengaruh Penerapan Model Pembelajaran Quiz Team terhadap Peningkatan Keberhasilan Pembelajaran PAI di Sekolah Menengah Pertama - Nihayah, Hamidatun; Isroani, Farida; Rohmawati, Umma (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study was to test the application of the Quiz Team learning model to increase the success of Islamic Religious Education learning at Al-Fatimah Junior High School Bojonegoro. This research is quantitative. The research sample was taken from class VIII SMP Al-Fatimah Bojonegoro. Collecting data was obtained by observation, interviews, tests, documentation, and questionnaires. The results showed an effect of implementing the Quiz Team learning model on increasing student learning success. The results of data analysis evidence this through testing to determine whether there is an influence between the X variable and the Y variable, then the data is processed in the product-moment “r” formula, which is finally known to have rxy = 0.601.